Neurosyphilis in China: A Systematic Review of Cases From 2009–2021 - Du, Fang-Zhi; Zhang, Hai-Ni; Li, Jing-Jing; Zheng, Zhi-Ju; Zhang, Xu; Zhang, Rui-Li; Wang, Qian-Qiu (Frontiers in Medicine, 2022)
Considered the increased threaten of neurosyphilis in China, a review on cases reported in the literature to describe the clinical epidemiological characteristics of neurosyphilis cases, may be beneficial to the early detection and management strategies of neurosyphilis for clinicians. We searched the literature on Chinese neurosyphilis cases published from January 1, 2009 to December 31, 2021, described their clinical epidemiological characteristics and calculated the prevalence of neurosyphilis amongst other associated diseases, according to the individual study criteria. A total of 284 studies including 7,486 neurosyphilis cases were included. No meta-analysis was performed due to the heterogeneity of the data. Among 149 case reports and 93 retrospective case series studies, the main clinical manifestation of 3,507 neurosyphilis cases was cerebral parenchymal syphilis (57.3%), followed by asymptomatic neurosyphilis (16.7%), meningovascular syphilis (13.6%), meningitis syphilis (7.7%) and ocular syphilis (2.8%), etc. In addition, the initial diagnosis was incorrect in 53.2% patients, and the most frequent misdiagnoses were mental disorders (26.5%), stroke (15.9%), cognitive impairment (9.0%), etc. The positive or abnormal rates of cerebrospinal fluid nontreponemal and treponemal tests, white blood cell counts and protein concentrations were 74.2%, 96.2%, 61.5% and 60.9%, respectively. Aqueous penicillin was the first choice for treatment in 88.3% cases, and 81.7% and 50.0% patients had response in the improvement of symptoms and serological effective in CSF, respectively. Among 26 studies on neurosyphilis patients amongst other associated diseases, the prevalence of neurosyphilis amongst central nervous system infectious diseases, syphilis-associated neurological symptoms, serofast status, coinfected with human immunodeficiency virus were 10.6%-30.1%, 23.2%-35.5%, 9.8%-56.1%, and 8.9%, respectively. In summary, the lack of early detection of neurosyphilis cases remains a clinical challenge. The high rate of misdiagnosis and high prevalence of neurosyphilis amongst associated diseases strongly remind clinicians to focus on the early detection among suspected cases. Besides, the standard treatment regimen and long-term follow-up, which complied with guideline should be provided. Further prospective studies are urgent to better delineate the clinical epidemiological characteristics of neurosyphilis in China.